2008
DOI: 10.1136/bjsm.2008.052100
|View full text |Cite
|
Sign up to set email alerts
|

Vibration therapy reduces plasma IL6 and muscle soreness after downhill running

Abstract: VT reduces muscle soreness and IL6. It may stimulate lymphocyte and neutrophil responses and may be a useful modality in treating muscle inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
74
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 24 publications
5
74
0
1
Order By: Relevance
“…These differences are important because the upper and lower body musculature may respond differently and different levels of vibration may elicit different responses. Whereas some researchers 20,21 have reported a decrease in muscle-pain rating (eg, DOMS intensity), they also have shown that PPTs were not different with vibration treatment, which is consistent with our observations. Another consideration is sex differences.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…These differences are important because the upper and lower body musculature may respond differently and different levels of vibration may elicit different responses. Whereas some researchers 20,21 have reported a decrease in muscle-pain rating (eg, DOMS intensity), they also have shown that PPTs were not different with vibration treatment, which is consistent with our observations. Another consideration is sex differences.…”
Section: Discussionsupporting
confidence: 83%
“…In their study of women only, Dannecker and Sluka 29 reported similar results in PPT measures, showing an increase in sensitivity up to 2 days after exercise, but did not have a WBV intervention. Researchers 17,[20][21][22] investigating men only have reported mixed results for different measures along with a different training status of male participants. More research using pain measures after DOMS is needed to determine if responses differ between sexes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…DOMS often develops after resistance training especially after the intensity and volume of training are increased, the order of exercise is changed or a new training regime is performed [4]. Numerous interventions aimed at alleviating DOMS has been proposed like Transcutaneous Electrical Nerve Stimulation (TENS) [5], ultrasound [6] and the administration of aspirin and other anti-inflammatory drugs [7], steroids [8] and vitamin C and other antioxidants [9].…”
Section: Introductionmentioning
confidence: 99%